Multimodal interventions (chewing gum, early oral hydration and early mobilisation) on the intestinal motility following abdominal gynaecologic surgery. Issue 13 (13th April 2013) - Terzioglu, Fusun; Şimsek, Sevgi; Karaca, Kubra; Sariince, Nilay; Altunsoy, Pinar; Salman, Mehmet Coskun
<x xml:space="preserve">Abstract</x> Aims and objectives To determine the effects of chewing gum, early oral hydration and early mobilisation on the time of first bowel sounds, first passage of flatus and first defecation following abdominal gynaecologic surgery. Background A major complication of abdominal surgical procedures is paralytic ileus which results in patient discomfort, prolonged length of hospital stay and increased cost of treatment. Design Prospective randomised case–control study. Methods Women who underwent abdominal gynaecological surgery for benign disorders under general anaesthesia were randomised into eight groups according to different combinations of interventions consisting of chewing gum, early oral hydration and early mobilisation. The effects of these interventions on the time of first bowel sounds, first passage of flatus and first defecation following abdominal gynaecologic surgery were investigated. The data were analysed using chi‐square tests, t‐test for independent samples, Tukey's HSD test, pairwise comparison test, one‐way analysis of variance. Results It was found that the time when bowel sounds were heard was shorter, the time first passage of flatus was shorter and first defecation occurred earlier in the 1st group of women who chew gum, were hydrated orally and were mobilised early after surgery than the other groups. It was also determined that these periods were longest in the women who did not receive any intervention and received the routine hospital care when compared with other groups. Duration of hospital stay was shorter in the women who chew gum, were hydrated orally and were mobilised early than the other groups. Conclusions Early oral feeding, early mobilisation and chewing gum are effective methods in terms of preventing paralytic ileus following abdominal gynaecological surgery, improving patient comfort and shortening the duration of hospitalisation. Relevance to clinical practice Nurses may cause early recovery, improve the patient comfort, prevent paralytic ileus and shorten the duration of hospitalisation after gynaecologic abdominal surgery by recommending gum chewing, early mobilisation and early hydration.